Descriptive epidemiology of sickle cell disease in Tennessee: population-based estimates from 2008 to 2019 - Plaxco, Allison P.; Hankins, Jane S.; Davis, Robert; Dudley, Judy; Young, Amanda J.; Mukhopadyay, Ayesha; Carroll, Yvonne; Aguinaga, Maria del Pilar; Takemoto, Clifford M.; Nolan, Vikki G.; Ray, Meredith A.; Wiese, Andrew; et al. (Frontiers in Hematology, 2023)
Introduction: The Sickle Cell Data Collection Program (SCDC) is a multi-state initiative utilizing multiple data sources to estimate population prevalence of Sickle Cell Disease (SCD) with the goal of improving quality of life and health outcomes among those affected. SCDC in Tennessee operates as a multi-site, interdisciplinary team using multiple sources of data to learn more about SCD in Tennessee.Methods: This analysis characterizes the number, demographics, and proximity to specialty care of individuals living with SCD in Tennessee who have been covered by Medicaid or identified by newborn screening. We compared demographic patterns of individuals with SCD living in rural areas with those living in urban areas, as well as those living in counties contributing more than 50 individuals to the cohort, respectively, to demographic patterns of individuals with SCD in the rest of the state, using Chi-Square or Fisher's exact tests.Results: Findings show that overall, 66.1% of all SCD patients identified through newborn screening were residents of Davidson and Shelby counties at the time of birth, and 81.8% of those identified through Medicaid claims lived in Davidson,